The first troglobitic Cryptops (Trigonocryptops) (Chilopoda: Scolopendromorpha) from South America and the description of a non-troglobitic species from Brazil - de Ázara, Ludson Neves; Ferreira, Rodrigo Lopes (Zootaxa, 2013)
Cryptops (Trigonocryptops) iporangensis n. sp., and C. (T.) hephaestus n. sp. are described from SE Brazil. C. (T.) iporangensis n. sp. presents highly troglomorphic characters and is described from a remarkable cave system located in Sao Paulo State, the Areias cave system, from were other 16 troglobitic species are also known. C. (T.) hephaestus n. sp. was described on specimens collected in three caves of the “Quadrilátero Ferrífero” (Iron quadrangle), in Minas Gerais State, but does not presents a clear specialization to subterranean habitat. The new troglobitic species can be separated from other species of Cryptops (T.) from Brazil and all troglobitc species of the genus Cryptops by presenting incomplete paramedian sutures on tergites, antennal article 1 with an inverted Y-shaped suture on its proximal part and distal spinose processes on ultimate leg. C. (T.) hephaestus differs from the other species of Cryptops (Trigonocryptops) from Brazil by presenting anterior oblique sutures on tergites 2-7 and posterior oblique sutures on tergites 1-3. Cryptops (Cryptops) galatheae Meinert, 1886 is moved here to the subgenus Trigonocryptops.